Alliances Operational Framework, Initiatives and Key Challenges. Issue 1 (March 2020) - Bukhari, Faheem; Hussain, Saima
Alliances and loyalty programmes play an important role in building brand awareness and increasing customer loyalty. An effective alliance initiative in the credit card domain strengthens the product's features by offering value to current and potential credit card users. The purpose of this case study is to highlight the holistic alliance roadmap developed by the local bank visa credit card team. The data have been acquired from the field. This real-life example highlights several challenges and raises questions about how to measure success in alliance initiatives and the lessons learned from the experience, especially regarding strategy modification.